Symptomatic osteonecrosis in children treated for Hodgkin lymphoma: A population-based study in Sweden, Finland, and Denmark - Giertz, Mia; Aarnivala, Henri; Michelsen, Sascha Wilk; Björklund, Caroline; Englund, Annika; Grönroos, Marika; Hjalgrim, Lisa Lyngsie; Huttunen, Pasi; Niinimäki, Tuukka; Penno, Eva; Pöyhönen, Tuuli; Raittinen, Päivi; et al. (WILEY, 2025)
Background: Osteonecrosis (ON) is a potentially disabling skeletal complication of cancer treatment. Although symptomatic osteonecrosis (sON) is well-known in acute lymphoblastic leukemia (ALL), with an incidence around 6%, studies on sON in pediatric Hodgkin lymphoma (HL) are scarce. The aim of this study was to examine the incidence, risk factors, and outcome of sON in children treated for HL.
Procedure: A total of 490 children under 18, diagnosed with HL between 2005 and 2019 in Sweden, Finland, and Denmark were eligible for the study. Data on patient characteristics, HL treatment, and development of sON were collected from patients' medical records. Magnetic resonance imaging scans were used to establish ON diagnosis and grade ON according to the Niinim & auml;ki grading system.
Results: Cumulative 2-year incidence of sON among the 489 included patients was 5.5% (n = 30). The risk for developing sON was higher for those with older age (odds ratio [OR] 1.25, 95% confidence interval [CI]: 1.05-1.49, p < .010), female sex (OR 4.45, CI 1.87-10.58, p < .001), high total cumulative glucocorticoid (GC) doses (OR 1.76, 95% CI: 1.21-2.56, p = 0.003), and advanced HL (OR 2.19, 95% CI: 1.03-4.65, p = .042). Four (13.3%) patients underwent major surgical procedures and 13 (43.3%) had persistent symptoms due to ON at follow-up.
Conclusions: This study shows that sON is as common in pediatric HL as in pediatric ALL, with risk factors such as older age, female sex, high cumulative GC doses, and advanced HL. Future HL protocol development should aim to reduce the burden of ON by modifying GC treatment.